Cultural Prototypes and Differences in Simulation Debriefing. Issue 4 (August 2018) - Ulmer, Francis F.; Sharara-Chami, Rana; Lakissian, Zavi; Stocker, Martin; Scott, Ella; Dieckmann, Peter
Abstract : Introduction: Culture is believed to play a role in education, safety, and patient outcome in healthcare. Hofstede's culture analysis permits a quantitative comparison between countries, along different culture dimensions, including power distance (PD). Power distance index (PDI) is a value reflecting social hierarchy in a country. We sought to explore the relation between PDI and self-reported behavior patterns of debriefers during simulation debriefings. We determined six culture-relevant debriefing characteristics and formulated six hypotheses on how these characteristics correlate with national PDIs. Methods: Low-PDI countries have a PDI of 50 or less, and high-PDI countries have a PDI of 51 or greater as defined by Hofstede. Interviews with simulation debriefers were used to investigate culture-relevant debriefing characteristics: debriefer/participant talking time, debriefer/participant interaction pattern, debriefer/participant interaction style, debriefer/participant initiative for interactions, debriefing content, and difficulty with which nontechnical skills can be discussed. Results: During debriefing, in low-PDI countries, debriefers talked less and used more open-ended questions and focused more on nontechnical issues than on medical knowledge and simulation participants initiated most interactions. In low-PDI countries, debriefers felt that participants interacted more with each other and found it easier to address nontechnical skills such as speaking-up. Conclusions: Our results supported our hypotheses. National culture is related to debriefing practice. There is a clear relation between PDI and debriefer-participant behavior patterns as described by debriefers. The higher the PDI of a country, the more the debriefer determines the course of the debriefing and the more difficult it becomes to address nontechnical skills. Abstract : Supplemental digital content is available in the text.